Análisis de la emisión de títulos de crédito por impuestos municipales y su impacto en el Gadmic Pujilí en el período 2019 – 2022. - Chipugsi Calero, Wilson Santiago (2023)
The economic autonomy of the municipality of Pujilí is influenced by the dependence on the Ecuadorian state and the budgetary allocations that it provides. The research project studied the analysis of the issuance of debt securities for municipal taxes and the impact on the income of the GADMI of the Canton Pujilí during the years 2019 to 2022, for which a descriptive research was used through a quantitative approach that allowed the analysis of the information provided by the Decentralized Autonomous Government of Canton Pujilí, where the different types of taxes used to collect revenue were evidenced, it was established through the analysis of budget, income and expenditure bonds, while the taxes used were On Income, Profits and Capital Gains; Property Tax, Excise of Goods and Services; and Miscellaneous. Of which, the property tax has been the most relevant with respect to the others analyzed, generating income of $817,179.32, which represents 81% of the total income, which for 2022 was $1,013,119.11. On the other hand, it was possible to determine through a statistical methodology that there is a moderate correlation coefficient regarding the impact of taxes on total revenues. The GADMIC is economically dependent on the allocations granted by the central government, donations, and credits; since it does not have sufficient collection capacity like the vast majority of Municipal GADs, which has generated the non-compliance of services. However, it is an institution with a significant population level. It can create rates to recover lost taxes, such as in the case of the Municipal Patent, to agricultural activities and replace them with others of equal or greater importance. Therefore, it can improve its level of effective collection.